DNA methyltransferase expression (DNMT1, DNMT3a, and DNMT3b) as a potential biomarker in age-related macular degeneration - Camacho, Pedro (2025)
Background/Objectives: Age-related macular degeneration (AMD) is a global cause of vision loss, with limited therapeutic options highlighting the need for effective biomarkers. This study aimed to characterize plasma DNA methyltransferase expression (DNMT1, DNMT3A, and DNMT3B) in AMD patients and explore divergent expression patterns across different stages of AMD. Methods: Thirty-eight AMD patients were prospectively enrolled and stratified by disease severity: eAMD, iAMD, nAMD, and aAMD. Comprehensive ophthalmological assessments included best-corrected visual acuity, digital color fundus photographs, and Spectral Domain Optical Coherence Tomography. Peripheral blood samples were collected for RNA extraction and qRT-PCR to access epigenetic effectors’ transcriptional expression, namely DNMT1, DNMT3A, and DNMT3B genes. The collected data were analyzed using IBM SPSS 29. Results: DNMT1 expression was significantly downregulated in late AMD (−0.186 ± 0.341) compared to early/intermediate AMD (0.026 ± 0.246). Within late AMD, aAMD exhibited a marked downregulation of DNMT1 (−0.375 ± 0.047) compared to nAMD (0.129 ± 0.392). DNMT3A and DNMT3B showed similar divergent expression patterns, correlating with disease stage. Conclusions: This study identified stage-specific transcriptional differences in DNMT expression, emphasizing its potential as a biomarker for AMD progression and a target for future research into personalized therapeutic strategies.